![image](https://tex.z-dn.net/?f=3+x%5E%7B2%7D+%2B2x-1%3C0+%5C%5C+3+x%5E%7B2%7D+%2B2x-1%3D0+%5C%5C+a-b%2Bc%3D0+%5C%5C+%3D%3E+x_%7B1%7D+%3D-1%2C+x_%7B2%7D%3D+%5Cfrac%7B1%7D%7B3%7D+%5C%5C+x+%28-1%3B+%5Cfrac%7B1%7D%7B3%7D+++%29)
x_{1} =-1, x_{2}= \frac{1}{3} \\ x (-1; \frac{1}{3} )" alt="3 x^{2} +2x-1<0 \\ 3 x^{2} +2x-1=0 \\ a-b+c=0 \\ => x_{1} =-1, x_{2}= \frac{1}{3} \\ x (-1; \frac{1}{3} )" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+x%5E%7B3%7D+-5+x%5E%7B2%7D+%2B6x+%5Cleq+0+%5C%5C+x%5E%7B3%7D+-5+x%5E%7B2%7D+%2B6x%3D0+%5C%5C+x%28+x%5E%7B2%7D+-5x%2B6%29%3D0+%5C%5C++x_%7B1%7D+%3D0+%5C%5C+x%5E%7B2%7D+-5x%2B6%3D0+%5C%5C+a%2Bb%2Bc%3D0+%5C%5C+%3D%3E+x_%7B2%7D+%3D1%2C+x_%7B3%7D%3D6+%5C%5C+x%28-+%5Cinfty%3B0%5D+u+%5B1%3B6%5D)
x_{2} =1, x_{3}=6 \\ x(- \infty;0] u [1;6]" alt=" x^{3} -5 x^{2} +6x \leq 0 \\ x^{3} -5 x^{2} +6x=0 \\ x( x^{2} -5x+6)=0 \\ x_{1} =0 \\ x^{2} -5x+6=0 \\ a+b+c=0 \\ => x_{2} =1, x_{3}=6 \\ x(- \infty;0] u [1;6]" align="absmiddle" class="latex-formula">